(untitled) (Avocetta, 2024)
Territorial songbirds use singing as an interactive social signal during territorial interactions. Considerable information has been accumulated about the communication of passerine birds in the context of territorial competition. Most of such data, however, were gathered in the northern temperate zone. Only a few studies have been conducted in the tropical zone. In this study, we describe for the first time the vocal and territorial behaviour of the Puff-throated Babbler Pellorneum ruficeps, a South Asian tropical resident bird. We recorded spontaneous vocalization simulated territorial intrusion by broadcasting different vocalizations at territories. We played back different types of conspecific vocalizations to territorial males: (1) male simple song, (2) male complex song, and (3) duet. Depending on context, there were three types of male vocalizations: simple song, complex song, and subsong. While singing spontaneously, males produced a simple song of 2–3 elements, repeated at a rate of 10–12 songs per minute. Males could respond to playback with complex songs, which are much more elaborate and longer (up to 5–10 seconds) vocalization emitted at a rate of approximately one song per minute. Subsong is the most commonly heard vocalization during playback-simulated territorial intrusion. Females could acoustically respond to playback along with the males, forming a duet. While duetting, females produced a sequence of identical broadband elements (trills) overlapping the male complex song. In response to simple song playback, males sang, approached the loudspeaker, and flew around it. Males reacted much more strongly when presented with the playback of complex songs. They sang more complex songs, performed more flyovers, and produced subsongs. Therefore, complex songs are an aggressive signal used in the context of territorial competition. We observed male-female duets in response to complex song playback only. Males sang more actively and performed more flyovers in response to duets than to complex songs. We thus assumed that the duet is a more aggressive signal than the complex song.